Kidney biopsy in AA amyloidosis: impact of histopathology on prognosis. (3rd July 2017) - Kendi Celebi, Zeynep; Kiremitci, Saba; Ozturk, Bengi; Akturk, Serkan; Erdogmus, Siyar; Duman, Neval; Ates, Kenan; Erturk, Sehsuvar; Nergizoglu, Gokhan; Kutlay, Sim; Sengul, Sule; Ensari, Arzu; et al.
Abstract: In AA amyloidosis, while kidney biopsy is widely considered for diagnosis by clinicians, there is no evidence that the detailed investigation of renal histopathology can be utilized for the prognosis and clinical outcomes. In this study, we aimed to obtain whether histopathologic findings in kidney biopsy of AA amyloidosis might have prognostic and clinical value. This is a retrospective cohort study that included 38 patients who were diagnosed with AA amyloidosis by kidney biopsy between 2005 and 2013.The kidney biopsy specimens of patients were evaluated and graded for several characteristics of histopathological lesions and their relationship with renal outcomes. Segmental amyloid deposition in the kidney biopsy was seen in 29%, global amyloid deposition in 71, diffuse involvement of glomeruli in 84.2%, focal involvement in 7%, glomerular enlargement in 53%, tubular atrophy in 75% and interstitial fibrosis in 78% of patients. Histopathologically, glomerular enlargement, interstitial fibrosis, tubular atrophy, interstitial inflammation and global amyloid deposition were significantly associated with lower estimated glomerular filtration rate (eGFR) ( p = .02, p < .001, p = .001, p = .009, p = .002, respectively) in univariate analysis. In multivariate analysis, tubular atrophy was the only predictor of eGFR ( p = .019 B = −20.573). In the follow-up at an average of 27 months, 18 patients developed end-stage renal disease (ESRD). Among them, global amyloid deposition was the only risk factor for the development of ESRD ( p = .01, OR = 18.750, %95 CI= 2.021–173.942). This is the first study showing that the histopathological findings in kidney biopsy of AA amyloidosis might have a prognostic and clinical value for renal outcomes.